Orpotrin: A novel vasoconstrictor peptide from the venom of the Brazilian Stingray Potamotrygon gr. orbignyi - Conceicao, Katia; Konno, Katsuhiro; Melo, Robson L.; Marques, Elineide E.; Hiruma-Lima, Clélia Akiko [UNESP]; Lima, Carla; Richardson, Michael; Pimenta, Daniel C.; Lopes-Ferreira, Monica (Elsevier B.V., 2006)
Characterization of the peptide content of venoms has a number of potential benefits for basic research, clinical diagnosis, development of new therapeutic agents, and production of antiserum. In order to analyze in detail the peptides and small proteins of crude samples, techniques such as chromatography and mass spectrometry have been employed. The present study describes the isolation, biochemical characterization, and sequence determination of a novel peptide, named Orpotrin from the venom of Potamotrygon gr. orbignyi. The natural peptide was shown to be effective in microcirculatory environment causing a strong vasoconstriction. The peptide was fully sequenced by de novo amino acid sequencing with mass spectrometry and identified as the novel peptide. Its amino acid sequence, HGGYKPTDK, aligns only with creatine kinase residues 97-105, but has no similarity to any bioactive peptide. Therefore, possible production of this peptide from creatine kinase by limited proteolysis is discussed. Taken together, the results indicate the usefulness of this single-step approach for low molecular mass compounds in complex samples such as venoms. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: orpotrin; Potamotrygon; venom; stingrays; vasoconstriction; de novo sequencing; natural peptides; creatine kinase